The Frasnian, Central Iran: biostratigraphy, facies analysis, paleoenvironment and sea level changes - Alizadeh, Ava; Hashmie, Afshin; Ghotbi, Neda (Journal of Himalayan Earth Sciences, 2021)
Two section in Bahram Formation for biostratigraphy, lithofacies, facies, paleoenvironment and sequence stratigraphy were studied. In this article to with the sequence stratigraphy of the Upper Devonian (Frasnian) Bahram Formation for this reason micro/lithofacies analysis of the sediments in the south toward northeastward part of the main Iran plate Mountains. According to stratigraphic distribution Bahram Formation at the study sections is of Frasnian stage, based on the occurrence of Umbella algae species in Shaftalugaltan section and conodonts in Sar-e-Ashk section. The main bioclastic components of the Bahram Formation are brachiopods, algae, bryozoans, corals, gastropods and fragment fossil. Microscopic investigation confirms the presence of eleven petro/microfacies typical for upward shallowing trend from in five micro/lithofacies belts shallow-open marine to shoal, restricted lagoon, and toward tidal flat and finally to near-shore depositional environments were identified. According to the evidence of environmental interpretations, we reconstructed a mix carbonate–siliciclastic shallow-water shelf mainly represented by its middle and inner sectors. The vertical expansion of the investigated litho/petro/microfacies provide for 3rd- order cyclic in the Bahram Formation. Comparison of the recommended sedimentary sequences with those reported in Iranian plate and the local relational change sea-level curves related, well with the worldwide change sea-level curves.